تطوير معجم بيولوجيا على أساس أندرويد في المواد اللافقارية لطلاب مدرسة الثانوية للصف العاشر ببرنامج الرياضية والعلوم الطبيعية - Dwi Maihidin Pahlifi; Afreni Hamidah; Mia Aina (Abjadia, 2018)
اللافقاريات هي واحدة من المواد التي يجب دراستها في البيولوجي للصف العاشر. في دراسة علم الأحياء، وخاصة في مادة اللافقاريات، تم العثور على العديد من المصطلحات باستخدام اللغة اللاتينية أو العلمية المتعلقة باللافقاريات. كثير من الطلاب يجدون صعوبة في متابعة مواد اللافقاريات، وخاصة في فهم شروط بنية الجسم من شوكيات الجلد و المفصليات التي غالبا ما يجدونها عندما يحدث التعلم. وبالتالي، لمعرفة معنى المصطلحات في المواد اللافقارية، يمكن للطلاب استخدام القواميس التي تستخدم اللغة اللاتينية والإندونيسية على أساس أندرويد ومجهزة أيضًا بالصور كمؤيدين. تم إجراء هذا البحث في مدرسة الثانوية الحكومية 1 في مدينة جامبي. تستخدم هذه الدراسة نموذج تطوير (ADDIE) الذي يتكون من خمس مراحل، هي: التحليل والتصميم والتطوير والتنفيذ والتقييم. نوع البيانات في هذه الدراسة هو البيانات الكمية، وهي البيانات التي تم الحصول عليها من تقييم استبيان الطلاب والبيانات النوعية، وهي البيانات التي تم الحصول عليها من فريق التحقق، وهم خبراء الإعلام وخبراء المواد. المنتجات التي تم تطويرها والتحقق من صحتها من قبل فريق من الخبراء يتألف من خبراء المواد وخبراء وسائل الإعلام، واختبرت مجموعات صغيرة ومجموعات كبيرة. تم تنفيذ نتائج التحقق من قبل الخبير المادي مرتين وتم الحصول على النسبة النهائية من 87.50٪ مع معايير جيدة للغاية وتم التحقق من صحة من قبل خبراء الإعلام 3 مرات، وكانت النسبة المئوية لجدوى المنتج 93.75٪ في معايير جيدة جدا. كانت النسبة المئوية للمحاكمات الجماعية الصغيرة لـ 8 من طلاب ببرنامج الرياضية والعلوم الطبيعية 84.01٪ في معايير جيدة للغاية وكانت النسبة المئوية للمحاكمات الجماعية الكبيرة لـ18 من طلاب ببرنامج الرياضية والعلوم الطبيعية 85.56٪ مع فئات جيدة جدًا. استنادًا إلى تحليل البيانات الكمية والنوعية، يمكن استنتاج أن المنتج الذي تم تطويره في شكل معجم بيولوجي يستند إلى أندرويد في مواد اللافقاريات للطلاب من الفئة مدرسة الثانوية الصف العاشر ببرنامج الرياضية والعلوم الطبيعية من الممكن استخدامه في عملية التعلم. Invertebrates is one of the compulsory materials in Biology lesson of class X. In studying biology,  there are  lots of terms using Latin or scientific language related to invertebrates. Many students have difficulty in learning Invertebrates material, especially in understanding the terminology section of the body structure of Echinoderms and Arthropods. Thus, to determine the meaning of the terms in these invertebrates materials students can use a dictionary that provides Latin and Indonesian languages based on Android and is also equipped with supporting images. This research was conducted at Senior High School 1 Jambi. This study aims to make learning media in the form of dictionary-based android biology in invertebrate material and test their feasibility with a small group trial. This study using ADDIE development model consisting of five stages: analysing, designing, developing, implementing and evaluating. The type of data in this study is  a quantitative data which is obtained from the assessment of student questionnaire and qualitative data that is obtained from the validation team who are media and subject matter experts. The products have been developed and validated by a team of experts consisting of subject matter experts and media experts, tested to small groups and large groups. The results of the validation by subject matter experts which held 2 times gain the final percentage 87.50% in the criteria very well and the validation by media experts conducted 3 times, produces a percentage of 93.75% and the  product eligibility criteria is very well. The percentage of small group trial to 8 students MIPA is 84.01% in the criteria very well and the percentage of large groups of trials to 18 students MIPA is 85.56% in the excellent category. Based on the quantitative and qualitative data analysis, it can be concluded that the products developed in the form of the Dictionary of Biology Android based on Material of  Invertebrates for High School Students of  X Graders in Science Class is eligible to be implemented in the learning process..